Impact of agricultural diversity and market accessibility on dietary outcomes for households, women, and children in Bangladesh - Begum, Musammet Rasheda; Hasnine, Injamamul; Barua, Klinton; Khan, Md Shafiqul Islam (International Journal of Agricultural Research, Innovation and Technology, 2025)
Diversified agricultural production increases household food diversity, especially in developing nations where subsistence farming is prevalent. The goal of this study was to determine the factors associated with farm production, commercialization, livestock rearing, and socio-demographic status on dietary diversity of households (HDD), women (WDD) and children (CDD). Data were obtained from 300 randomly selected households using two-stage random sampling techniques. HDD, WDD and CDD were measured using 24-hour dietary recall data. A binary logistic regression and negative binomial regression model were applied to find the significant factors associated with HDD, WDD, and CDD. The mean values of HDD, WDD, and CDD were 7.59, 6.62, and 4.74. Cereals were consumed by 99% of participants. The adequate and inadequate HDD of the participants were 49.3% and 50.7%. As farm production increases, the odds of HDD and CDD scores increase by 1.35 units and 18%. HDD and WDD were 0.26 and 032 times lower in households with six or fewer members compared to those with more than six members. The HDD and WDD were 4.33 and 7.92 times higher for attending market participation. The HDD and WDD were 0.16 and 0.36 times lower for the people who reared domestic animals. The WDD was 0.46 times lower for family income less than 25000 taka. The CDD score decreases by 0.61 with attending market participation. Better market access and farm production diversity can be used to increase HDD and WDD, whereas CDD increases with production diversity. The results emphasize the necessity of improving market access, family income and crop-livestock integration for improved nutrition. Int. J. Agril. Res. Innov. Tech. 15(1): 136-146, June 2025